Complete taxon sampling of the avian genus Pica (magpies) reveals ancient relictual populations and synchronous Late‐Pleistocene demographic expansion across the Northern Hemisphere. (27th February 2018) - Song, Gang; Zhang, Ruiying; Alström, Per; Irestedt, Martin; Cai, Tianlong; Qu, Yanhua; Ericson, Per G. P.; Fjeldså, Jon; Lei, Fumin
Abstract : Previous studies have suggested that bird populations in east Asia were less affected by Pleistocene climatic fluctuations than those in Europe and North America. However, this is mainly based on comparisons among species. It would be more relevant to analyse geographical populations of widespread species or species complexes. We analyzed two mitochondrial genes and two nuclear introns for all taxa of Pica to investigate 1) which Earth history factors have shaped the lineage divergence, and 2) whether different geographical populations were differently affected by the Pleistocene climatic changes. Our mitochondrial tree recovered three widespread lineages, 1) in east Asia, 2) across north Eurasia, and 3) in North America, respectively, with three isolated lineages in northwest Africa, Arabia and the Qinghai‐Tibet Plateau, respectively. Divergences among lineages took place 1.4–3.1 million yr ago. The northwest African population was sister to the others, which formed two main clades. In one of these, Arabia was sister to Qinghai‐Tibet, and these formed the sister clade to the east Asia clade. The other main clade comprised the North American and north Eurasian clades. There was no or very slight structure within these six geographical clades, including a lack of differentiation between the two North American species black‐billed magpie P. hudsonia and yellow‐billed magpie P. nutalli . Demographic expansion was recorded in the three most widespread lineages after 0.06 Ma. Asymmetric gene flow was recorded in the north Eurasian clade from southwestern Europe eastward, whereas the east Asian clade was rooted in south central China. Our results indicate that the fragmentation of the six clades of Pica was related to climatic cooling and aridification during periods of the Pliocene–Pleistocene. Populations on both sides of the Eurasian continent were similarly influenced by the Pleistocene climate changes and expanded concomitantly with the expansion of steppes. Based on results we also propose a revised taxonomy recognising seven species of Pica .